Multisystem Inflammatory Syndrome in Children Associated With Severe Acute Respiratory Syndrome Coronavirus-2 in an 8-Week-Old Infant. (11th November 2020) - Orlanski-Meyer, Esther; Yogev, Dotan; Auerbach, Adi; Megged, Orli; Glikman, Daniel; Hashkes, Philip J; Bar-Meir, Maskit
Abstract: We describe an 8-week-old infant with severe gastrointestinal symptoms, significant hypoalbuminemia, and mild carditis following asymptomatic infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). The infant's symptoms, including their temporal appearance, were consistent with multisystem inflammatory syndrome in children (MIS-C). A unique finding on colonic histology which may shed light on the pathogenesis of MIS-C was identified. The patient improved significantly following several anti-inflammatory treatments. The lag between the presentation of MIS-C and initial SARS-CoV-2 exposure, which may often be asymptomatic, together with the young age of our patient, makes this a challenging diagnosis. Clinicians should be aware of this entity, even in the neonatal and infantile age groups, to facilitate timely identification and treatment. Abstract : An 8-week-old infant with severe gastrointestinal involvement and mild carditis was diagnosed with multisystem inflammatory syndrome associated with severe acute respiratory syndrome coronavirus 2 following asymptomatic infection.